The Use of Predimenol for Nonspecific, Mild-to-Moderate Headache: Case Series - Rizaldy Taslim Pinzon; Andre Darmawan Wiyono (MEDICINUS, 2025)
Headache is a major healthcare concern worldwide. Adequate headache management is a widespread clinical concern, either using prescription or over-the-counter (OTC) nonsteroidal anti-inflammatory drugs (NSAIDs). The use of NSAIDs for headache has been associated with several risk of cardiovascular (CV), renal, and gastrointestinal (GI) complications.There were certain patients are at increased risk of using these agents. The use of NSAIDs results in small but consistent increases in the risk of cardiovascular events and kidney problem. We report case series of primary headache conditions with GI comorbidities. After careful history taking, neurological examination, and imaging, we used paracetamol and Predimenol for one week. The use of Predimenol was effective in reducing headache severity without any significant side effects.